The Role of The School Principle In Improving Teacher's Work Ethos In MIS Al Quba Medan - Widiyarti, Gemala; Rezeki, Ulfah Sari; Datten, Datten (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to describe the role of the principal in improving the work ethic of teachers at MIS Al Quba Medan. Data collection is done by conducting observations, interviews, and documentation. Data analysis used is descriptive qualitative analysis. The technique for checking the validity of the data used in this study uses source triangulation, namely by comparing the observed data with the interview data and comparing the interview results with the contents of a related document. The results showed: the role of the principal in improving the teacher's work ethic at MIS Al Quba Medan, the principal is able to create harmonious working relationships among teachers, is able to improve the teacher's work ethic through his role as Educator, Manager, Administrator, Supervisor, Leader, Innovator and Motivator. So that the vision and mission goals of the school can be carried out properly.